2011
DOI: 10.1074/jbc.m111.295840
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of S Phase Kinase-associated Protein 2 by NR4A Orphan Nuclear Receptor NOR1 in Vascular Smooth Muscle Cells

Abstract: Background:The nuclear receptor NOR1 serves a mitogenic role; however, the mechanisms underlying this activity remain poorly understood. Results: NOR1 induces Skp2 transcription, leading to a decrease in p27 protein abundance. Conclusion: Skp2 constitutes a NOR1-regulated gene, which contributes to the mitogenic activity of this nuclear receptor. Significance: These studies detail a novel transcriptional cascade regulating proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…A Skp2 adenoviral (Ad) expression construct 30 was titrated in order to maintain expression while minimizing potential off-target effects (data not shown). A titer of ~2000vp/cell resulted in robust expression of Skp2 as compared to GFP control, but had minimal effect on endogenous p27 kip1 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A Skp2 adenoviral (Ad) expression construct 30 was titrated in order to maintain expression while minimizing potential off-target effects (data not shown). A titer of ~2000vp/cell resulted in robust expression of Skp2 as compared to GFP control, but had minimal effect on endogenous p27 kip1 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HEK 293 cells were transiently transfected with a NOR1 or green fluorescent protein expression vector using Lipofectamine 2000 (Invitrogen, Grand Island, NY, http://www.lifetechnologies.com/) as described . RNA was collected with Trizol (Invitrogen, Grand Island, NY, http://www.lifetechnologies.com/) 48 hours after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…NR4A3-induced proliferation has been linked to regulation of cyclins D1 and D2 [174, 175] and S-phase kinase-associated protein 2 (Skp2) which results in decreased expression of the cyclin-dependent kinase inhibitor p27 [176]. A recent study showed that miR-638 is also a key regulator of smooth muscle cell proliferation by targeting NR4A3 which results in silencing of NR4A3-regulated genes involved in cell proliferation [177].…”
Section: Nr4a3 In Cellular Homeostasis and Diseasementioning
confidence: 99%